Exercise imagery: A systematic review of the empirical literature - Kossert, A. L.; Munroe-Chandler, K. (Journal of Imagery Research in Sport and Physical Activity, 2007)
A systematic review was conducted on the utilisation of mental imagery in its contribution to improvements in exercise performance and behaviour. Research into imagery use in exercise is in its infancy, and thus, there have been conceptual, measurement and methodological inconsistencies. The purpose of the current paper was to review the empirical literature thus far on exercise imagery. It was concluded that exercise imagery might indeed prove to be an effective tool in enhancing performance and adherence in physical activity programmes; however, the refinement of measurement tools is required in order to further evaluate its nature and efficacy. Furthermore, the employment of a recently developed conceptual model for the use of imagery in exercise offers a theoretical direction to future research contributions, and in the design of imagery interventions in the exercise domain.